Semito-Hamitic or Afro-Asiatic consonantism and lexicon: Episodes of a comparative research II: The “old school” of Egypto-Semitic (Part 1: Pre-war phase) - Takács, Gábor (Lingua Posnaniensis, 2021)
A retrospective account on the past of the comparative research on Semito-Hamitic / Hamito-Semitic (SH / HS, resp.) or Afro-Asiatic (AA) phonology (first of all consonantism, also root structure) and lexicon, segmented into episodes according to diverse (often overlapping in time) trends is now under way and will be presented part by part in a series of papers. Episode II evaluates the so-called “old school”, a rather introverted special trend of this domain (arbitrarily focusing on a comparison of just these two branches: Semitic and Egyptian), which split off from mainstream Semito-Hamitic studies at the end of the 19th century, more than a whole century ago. The present paper surveys the pre-war share (encompassing some half of a century), a blooming and most fruitful phase in the history of Egypto-Semitic studies.